Disentangling Important Factors in Service Quality: An Empirical Study in Vocational Higher Education at Bandung City - Pepi Zulvia; Hendrikus Tri Wibawanto Gedeona; Hafid Aditya Pradesa (Jurnal Ilmu Manajemen Advantage, 2022)
The purpose of this study, which is to reveal a comprehensive picture of the quality of these services in the data obtained from the evaluation of service quality from the perspective of its main users, namely students. This study was conducted using a quantitative method with a confirmatory factor analysis approach with a cross-sectional design. The proposed model is based on a current conceptualization of service quality, which suggests that service quality is a multidimensional and hierarchical construct. The validity value of the factor model shows good results so that the quality of higher education services can be reflected in nine aspects, namely (1) educational facilities, (2) reliability, (3) responsiveness, (4) empathy, (5) academic services information systems, ( 6) general facilities & infrastructure, (7) students' interests and activities, (8) library services, and (9) financial services. The results of the study reveal that responsiveness is the factor that best reflects service quality in higher education. While the score for general facilities and infrastructure is the aspect that is rated the lowest, especially on the factor regarding cleanliness in toilets and public facilities. The paper has value for the higher educational institute (HEI) seeking to improve the quality of services they provide.